Air Pollution and Autism Spectrum Disorder in Israel: A Negative Control Analysis. Issue 6 (November 2021) - Magen-Molho, Hadas; Weisskopf, Marc G.; Nevo, Daniel; Shtein, Alexandra; Chen, Shimon; Broday, David; Kloog, Itai; Levine, Hagai; Pinto, Ofir; Raz, Raanan
Abstract : Background: Residual confounding is a major concern for causal inference in observational studies on air pollution-autism spectrum disorder (ASD) associations. This study is aimed at assessing confounding in these associations using negative control exposures. Methods: This nested case-control study included all children diagnosed with ASD (detected through 31 December 2016) born during 2007–2012 in Israel and residing in the study area (N = 3, 843), and matched controls of the same age (N = 38, 430). We assigned individual house-level exposure estimates for each child. We estimated associations using logistic regression models, mutually adjusted for all relevant exposure periods (prepregnancy, pregnancy, and postnatal). We assessed residual confounding using postoutcome negative control exposure at age 28–36 months. Results: In mutually adjusted models, we observed positive associations with ASD for postnatal exposures to NOx (odds ratio per interquartile range, 95% confidence interval: 1.19, 1.02–1.38) and NO2 (1.20, 1.00–1.43), and gestational exposure to PM2.5-10 (1.08, 1.01–1.15). The result for the negative control period was 1.04, 0.99–1.10 for PM2.5, suggesting some residual confounding, but no associations for PM2.5-10 (0.98, 0.81–1.18), NOx (1.02, 0.84–1.25), or NO2 (0.98, 0.81–1.18), suggesting no residual confounding. Conclusions: Our results further support a hypothesized causal link with ASD that is specific to postnatal exposures to traffic-related pollution. Abstract : Supplemental Digital Content is available in the text.